Liolaemus melanops Burmeister and the subspecific status of the Liolaemus fitzingeri group (Sauria-lguanidae) - Cei, José Miguel Alfredo María (1975)
A new arrangement of the Patagonian lizards of the Liolaemus fitzingeri group is discussed. Three geographical forms are proposed: L. fitzingeri melanops Burmeister North of Rio Chubut; L. fitzingeri canqueli subsp. nov. from the volcanic Meseta Canquel, Central Chubut; L. fitzingeri fitzingeri (Dumeril et Bibrdn) from Southern Chubut and Santa Cruz territories. A redescription of L. fitzingeri melanops is given. Populations from Meseta Canquel, formerly considered by the author as L. fitzingeri melanops, are synonymized with L. fitzingeri canqueli subsp. nov.